The effectiveness of cartographic method as a tool in illustration of research data: a case study of Delta University, Abraka-Nigeria - Okosun, Oboh Satur (Geodesy and Cartography, 2017)
This research work examined the effectiveness of cartographic method as a tool in the illustration of research data, by examining the role cartographic method has over descriptive method, it effectiveness, and process involved; in Delta State University Abraka. In line with these a structured questionnaires were administered to 200 student from various levels of study; that is from 100 to M.sc level and some questionnaire were also administered to some lecturers of the department in other to obtain information on the effectiveness of cartographic method usage. The data generated where analysed using the spearman’s rank correlation and the student’s’ test. For the spearman rank analysis, the test revealed that the calculated t value (8.53) is greater than the tabulated t value (2.35) at 5% level of significance, the student‘t’ test analysis showed that the calculated t value (0.00) is less than the tabulated value (2.78) at 5% level of significance. The result of the research at the end of the day reveals that, there is a strong relationship within all the level of study based on the cartographic technique employed in research data illustration. On the other hand, with the use of statistical diagram and map, it shown that with the information extracted there is no strong relationship between the two methods. Based on the findings, recommendations were made on the use of cartographic method toward adequate coverage of the entire study topic.